Fifteenth-century studies. essays in honor of Edelgard E. DuBruck ; founder, Edelgard E. DuBruck ; consulting editor, William C. McDonald ; edited by Barbara I. Gusick and Edelgard E. DuBruck.: essays in honor of Edelgard E. DuBruck ; founder, Edelgard E. DuBruck ; consulting editor, William C. McDonald ; edited by Barbara I. Gusick and Edelgard E. DuBruck. Volume 32 : (2007) - Unknown
No abstract available